Analysis of Potential Cinnamomum zeylanicum Blume Essential Oil Against Alzheimer's Disease: A Molecular Docking Study - Muhammad Ja'far Shodiq; Farmindo Hartono; Siti Khaerunnisa; Abdulloh Machin (Universitas Airlangga, 2023)
Background: Alzheimer's Disease (AD) is a neurodegenerative disorder with progressive impairment of behavioural and cognitive functions and the most common cause of dementia. The pathophysiology of AD is associated with low acetylcholine, accumulation of amyloid beta plaque, and neurofibrillary tangles in the brain. Cinnamomum zeylanicum is known to have many medicinal properties, especially neuroprotective effects. Objective: This research was designed to determine the neuroprotective potential of the phytochemicals C. zeylanicum using an in silico study. Methods: There are 5 phytochemicals compounds of C. zeylanicum used in this study. It's qualified for Lipinski's rules of five and can cross blood brain barrier. The protein targets were AChE, BACE1, and GSK-3. Molecular docking and visualization were performed using Avogadro, AutoDock 4.2 PyMol and Biovia Discovery Studio 2019. Results: In silico results show that the main phytochemical compounds of C. zeylanicum Blume essential oil have great potency as an AD drug. The best interaction model of the compound was shown by trans-cinnamyl acetate and coumaric acid. Although the binding energy of the compounds is lower than AD drugs (donepezil, rivastigmine, galantamine), the binding energy is not much different from rivastigmine and galantamine. Conclusion: The phytochemical compounds of C. zeylanicum Blume essential oil have an effect as a neuroprotective agent for AD and should be investigated in future research.